2012
DOI: 10.1111/ics.12002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of a dioic acid‐based formulation on facial skin in an Indian population

Abstract: The aim of this work was to investigate the effects of 1,18-octadecen-9-dioic acid (dioic acid) and a Rumex occidentalis extract complex for their skin-lightening action in an Indian population. Prior to the clinical study, the efficacy of dioic as an inhibitor of melanogenesis was confirmed on dark-pigmented human melanocytes. As part of a 12-week vehicle-controlled clinical study, the skin-lightening effect of a test product containing 1% dioic acid, 2% of a Rumex occidentalis extract and sunscreens (SPF 15)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Moreover, synergistic effect of octadecenoic acid and plant extract of Rumex Occidentalis has been reported in reconstructed tanned epidermis [102], where the Rumex extract showed direct inhibition of tyrosinase activity [103].…”
Section: Acceleration Of Epidermal Turnover and Desquamationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, synergistic effect of octadecenoic acid and plant extract of Rumex Occidentalis has been reported in reconstructed tanned epidermis [102], where the Rumex extract showed direct inhibition of tyrosinase activity [103].…”
Section: Acceleration Of Epidermal Turnover and Desquamationmentioning
confidence: 99%
“…Suppression of melanin formation on purified tyrosinase and in melanocytes [108] Clinical study using magnesium-L-ascorbyl-2-phosphate cream resulted in lightening effect in 19 of 34 patients with chloasma or senile freckles [108] octadecenedioic acid Reduction in tyrosinase mRNA and protein expression concomitant with inhibition of melanogenesis [101] Studies on octadecenedioic acid resulted in a more even skin tone and overall lighter skin colour [102,142] ª POMC-related peptides [112], it is likely that alternative pathways can activate intracellular cAMP and induce melanogenesis. One alternative cAMP-dependent pathway that has been proposed to be active and turn on melanogenesis in these mice is the adrenergic receptor, especially since the POMC-deficient mice was shown to have an abnormally large adrenal gland [112,113].…”
Section: Retinoic Acidmentioning
confidence: 99%
“…While countless vehicle‐controlled studies have demonstrated about the benefit of actives over a vehicle alone and/or vs gold standard ingredients, clinical evidence about the benefits of a skin care routine remains scarce, despite the claimed benefits of using products as part of a regimen. Reported efficacy of regimens is available in the dermatological field, to address skin conditions such as acne, atopic dermatitis, or rosacea .…”
Section: Introductionmentioning
confidence: 99%
“…9 Typical actives include retinoids, [10][11][12] niacinamide, [13][14][15][16] kojic acid, 17 arbutin and derivatives, 18,19 bisabolol, 20 soybean trypsin inhibitors, 21 azelaic acid, 22 licorice derivatives such as Glabrene and isoliquiritigenin, 23 vitamin C derivatives and other antioxidants, 24 N-acetyl glucosamine, 25,26 N-undecy-10-enoyl-L-phenylalanine, 27 hydroxyacids 28,29 and octadecenedioic acid. [30][31][32] To develop new potential ingredients for skin-lightening products, we have focused on the inflammatory pathways involved in skin pigmentation. 33 Recently, it has been shown that a peptide comprising Lys-Glu-Lys (KEK), which was further modified with a proline attached to its N-terminus (PKEK) to stabilize its structure, reduces interleukin-6 and 8, tumor necrosis factor-a and cyclo-oxygenase gene expression in ultraviolet (UV) light-stimulated keratinocytes in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional routes include the use of sunscreens, but inhibition of melanocyte activity, reduction in melanosome transfer and dendricity together with the accelerated removal of melanin by inducing epidermal proliferation are typical 9 . Typical actives include retinoids, 10–12 niacinamide, 13–16 kojic acid, 17 arbutin and derivatives, 18,19 bisabolol, 20 soybean trypsin inhibitors, 21 azelaic acid, 22 licorice derivatives such as Glabrene and isoliquiritigenin, 23 vitamin C derivatives and other antioxidants, 24 N‐acetyl glucosamine, 25,26 N‐undecy‐10‐enoyl‐L‐phenylalanine, 27 hydroxyacids 28,29 and octadecenedioic acid 30–32 …”
Section: Introductionmentioning
confidence: 99%